Economic Growth and Household Expenditure Nexus: A Focus on Education and Health in South Africa - Mpundu, Mubanga; Mpundu, Mubanga; Diko, Nolutho (Richtmann Publishing, 2021)
The COVID-19 pandemic which was first recorded from China and spread globally in 2020 caused a massive response from many countries with most opting for national lockdowns. The move prohibited the movement of people across boarders so as to control and limit the spread of the virus. In developing countries, the move contributed to ill performing economies even before the pandemic was rampant. The study focused on analysing time series data with a focus on the effects of changes in final consumer consumption on health and education on gross domestic product per capita. A Vector Error Correction Model was used as a suitable displaying technique when the factors were found to be cointegrated. Numerous economic variables showed persistent upward or descending movement which could be created by stochastic patterns in incorporated variables. Results showed the error correction coefficient was statistically significant showing the speed at which GDP per capita returned to equilibrium because of changes in the independent variables. What was interesting from the results was the fact that final consumption expenditures on health and education where not negatively affected by shocks in the economy prior and during COVID-19. Consumers where still spending on the health and education as they are considered vital for the development and wellbeing of households even with reduced foreign direct investment observed.Â Investment into high return projects both in health and education should be funded more as they in turn tend to have a positive impact on production. Â Received: 4 March 2021 / Accepted: 15 June 2021 / Published: 8 July 2021